2016
DOI: 10.1007/s11270-016-3128-0
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Phosphate from Aqueous Solution Using Alginate/Iron (III) Chloride Capsules: a Laboratory Study

Abstract: Binding phosphate at participation of alginate/FeCl3 capsules was studied with laboratory experiments. The hydrogel microcapsules were obtained with the dropping-in method, by gelation of sodium alginate water solution by iron (III) chloride solution. Phosphate adsorption characteristics were studied in a static batch system with respect to changes in contact time, initial phosphates concentration, pH of solution, and temperature. After 24 h of the tests, average 87.5% of phosphate ions were removed from the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…That group includes those isotherms where no competitive action between the adsorbate and solvent occurs. The same form of isotherms was achieved by those authors, who studied phosphorus adsorption processes on goethite [13,15] and on other iron-containing adsorbents, e.g., the alginate/Fe 3+ hydrogel beads [33], lignocellulose [43], wood biomass partially impregnated with carboxylmethylcellulose, and FeCl 3 [44,45] or surfactant-modified natural zeolite [46]. As a result of studies on adsorption of phosphorus on a mix of iron oxide and gypsum, an S-type adsorption isotherm was obtained, characteristic for arrangements where the solvent is strongly adsorbed.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…That group includes those isotherms where no competitive action between the adsorbate and solvent occurs. The same form of isotherms was achieved by those authors, who studied phosphorus adsorption processes on goethite [13,15] and on other iron-containing adsorbents, e.g., the alginate/Fe 3+ hydrogel beads [33], lignocellulose [43], wood biomass partially impregnated with carboxylmethylcellulose, and FeCl 3 [44,45] or surfactant-modified natural zeolite [46]. As a result of studies on adsorption of phosphorus on a mix of iron oxide and gypsum, an S-type adsorption isotherm was obtained, characteristic for arrangements where the solvent is strongly adsorbed.…”
Section: Discussionsupporting
confidence: 67%
“…In the case of alginate with modification by Fe 3+ , some adsorbents were produced for purifying water from oxygen anions containing Se 4+ , Cr 6+ , and As 5+ [30,31]. The literature refers to two similar formula obtained for adsorption of phosphate ions from the aquatic phase alginate/zirconium sulfate matrix, which has better sorptive qualities than powdered zirconium sulfate [32] and alginate/Fe 3+ beads [33].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of phosphate adsorption in Scheme 2 presents the creation route of this coordination structure on the surface of NP. Two surface oxygen groups of NP exist in intermediate I and II (shown in Scheme 3), by which the aminic hydrogen (NH) of diamine can form a doubly H-bonded composition to give hydroxyl (see structures 1 and 2, Schemes 2 and 3); subsequently, they are replaced with one oxygen of phosphate group (P 2 O 5 ) of NP [60][61][62]. It is confirmed that gray-to-black-colored particles that appeared on the recycled NP is hematite (Fe 2 O 3 ), which is released from NP during the reaction [63,64].…”
Section: Edx Analysismentioning
confidence: 99%
“…After chemical modification, it can be converted into adsorbents with anionic sorption capacity. By such modification using Fe(III) or Zr(IV) compounds, adsorbents for purifying water from oxygen anions containing Se(IV), Cr(VI) and As(V) [ 25 , 26 ] or P [ 27 , 28 ] compounds were obtained.…”
Section: Introductionmentioning
confidence: 99%